Compartment Syndrome During an Ischaemic Forearm Exercise Test. Issue 4 (1st August 2004) - Niepel, Graham G; Lowe, James; Wills, Adrian J
Abstract : THE CASE A 32-year-old man presented with a history of progressive exercise intolerance, exertional myalgia and cramps since childhood. He also complained of shortness of breath on exertion, without any orthopnoea. On examination he had mild proximal upper and lower limb weakness. His facial muscles and neck flexors were normal and there was no scapular winging. His tendon reflexes and sensory examination were normal. Serum creatine kinase (CK) levels were mildly raised at 493 IU/L (reference range < 180 IU/L). He underwent an ischaemic forearm exercise test, exercising for 40 s, and his effort was felt to be very good. However, later that afternoon he was reviewed because he was complaining of continuing pain in his forearm and inability to extend his fingers. He was treated with analgesia. CK levels were re-checked at this point and were markedly elevated at 38 000 IU/L. His symptoms persisted and he began to